2018
DOI: 10.3390/nano8050353
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Catalytic Reduction of 4-Nitrophenol Driven by Fe3O4-Au Magnetic Nanocomposite Interface Engineering: From Facile Preparation to Recyclable Application

Abstract: In this work, we report the enhanced catalytic reduction of 4-nitrophenol driven by Fe3O4-Au magnetic nanocomposite interface engineering. A facile solvothermal method is employed for Fe3O4 hollow microspheres and Fe3O4-Au magnetic nanocomposite synthesis via a seed deposition process. Complementary structural, chemical composition and valence state studies validate that the as-obtained samples are formed in a pure magnetite phase. A series of characterizations including conventional scanning/transmission elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 94 publications
2
27
0
1
Order By: Relevance
“…Recently, Au, Ag, Pt, and other noble metal nanocatalysts are recognized as promising catalysts for the removal of azo dyes by the virtue of high efficiency [18][19][20]. Among these noble metal nanomaterials, Au nanocrystals have been proven to be the optimal catalysts due to the excellent chemical and physical stability, tunable optical properties, high catalytic performances, and the surface plasmon resonance (SPR) properties [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Au, Ag, Pt, and other noble metal nanocatalysts are recognized as promising catalysts for the removal of azo dyes by the virtue of high efficiency [18][19][20]. Among these noble metal nanomaterials, Au nanocrystals have been proven to be the optimal catalysts due to the excellent chemical and physical stability, tunable optical properties, high catalytic performances, and the surface plasmon resonance (SPR) properties [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials that can efficiently use carbon dioxide from the air, capture toxic pollutants from water and degrade solid waste into useful products, are being developed. In line with this theme, seven representative articles [1][2][3][4][5][6][7] have been published in this Special Issue:…”
mentioning
confidence: 92%
“…Chen et al [5] reported the preparation of Fe 3 O 4 -Au magnetic nanocomposites using a well-developed Au seed deposition method. The increase of the quantity of the Au seeds attached to the surfaces of the Fe 3 O 4 hollow microspheres resulted in Fe 2p peaks shifting toward a lower binding energy and Au 4f peaks shifting towards a higher binding energy.…”
mentioning
confidence: 99%
“…Catalytic applications such as H 2 O 2 based reduction, CO oxidation are well known for Au‐Fe 3 O 4 nanomaterial. In 2018, Yang's group and Xing's group separately shown the reduction of nitrophenol by Au‐Fe 3 O 4 either synthesized via β‐cyclodextrin and ferrocene combination or solvothermal method at 200 °C . However, none of these methods show the effect of catalytic activity by the variation of gold and iron ratio in the nanomaterial.…”
Section: Introductionmentioning
confidence: 99%